GAPDH, Interferon γ, and Nitric Oxide: Inhibitors of Coronaviruses - Awan, Aashir (Frontiers in Virology, 2021)
As the Covid-19 pandemic enters into its second year, progress has been made against the SARS-CoV-2 virus with vaccine candidates showing efficacy against this latest coronavirus strain. However, this pandemic also presents a unique opportunity to investigate anti-viral therapies given the likely probability of another outbreak. One possible (and perhaps unlikely) therapeutic target could be GAPDH (glyceraldehyde-3-phosphate dehydrogenase). Studies have shown that a downregulation of GAPDH leads to a decrease in interferon gamma (IFNg) production (which has been shown to be an important cytokine response against coronaviruses and viruses in general). The previous coronavirus strain (SARS-CoV) does indeed downregulate this glycolytic enzyme (which also plays a role in gene expression of a varied set of genes by binding to their mRNA to affect stability) upon infection. Moreover, GAPDH is also upregulated by nitric oxide (NO), an inhibitor against both the SARS-CoV and SARS-CoV-2 viruses. Additionally, GAPDH has also been shown to be a negative transcriptional regulator of AT1R (angiotensin II receptor 1), which has been shown to bind ACE2 for eventual endocytosis of the complex implicating GAPDH’s potential role in the kinetics of coronavirus entry as well in downstream inflammatory signaling resulting from AT1R activation. Lastly, another important role for GAPDH in inflammation is its requirement in the assembly of the GAIT complex that is responsible for termination of IFNg-responsive genes. These observations would imply that sufficient levels of GAPDH are needed for immune responses to function properly during a coronaviral infection. By examining different coronavirus studies, this review explores GAPDH’s role as an inhibitor of coronaviruses (at the viral transcriptional level and also as a modulator of gene expression related to inflammation), and its signal transduction link to the IFNg and NO pathways.